ROLE OF CERTAIN PHYSICO-CHEMICAL PROPERTIES OF WATER ON ABUNDANCE OF TREMATO DE PARASITES OF CHANNA PUNCTATA (BLOCH) IN SONE BEEL, ASSAM INDIA - SINGH, NGASEPAM ROMEN; SHOMORENDRA, M.; KAR, DEVASHISH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2015)
Helminth parasite infection in fishes by trematode (Liver fluke : Parasitic flatworms having external suckers for attaching to a host) parasites can lead to severe change in nutrient content and may result in host mortalities and character of a water body may influence the parasitic fauna. Hence a study was carried out from January 2014 to December 2014 to find out the effect of physico-chemical characteristics of water on the abundance of trematode parasites of Channa punctata (Bloch) in Sone Beel, Assam, India. During the present investigation two species of trematodes were recorded. In the present study We had come across concurrent infections by two parasite species. Percentage abundance infection is positively correlated to pH (r = 0.688, p-0.05), Dissolved oxygen (DO mg/L) (r. = 0.847, p<0.01) and Water Temperature (WT) (r. = 0.720, p<0.01) but negatively correlated with Total Alkalinity (TA), Dissolved oxygen (DO mg/L) is positively correlated with pH (r= 0.668, p<0.05), Free carbon dioxide (FCO) is also positively correlated with pH ( r = 0.763, p<0.001), & Dissolved oxygen (DO mg/L) at r = 0.615, p<0.01, TA mg/L is negatively correlated with free carbon dioxide and water temperature strongly correlated with percentage abundance (r = 0.720, p<0.01), pH (r = 0.863, p<0.01), DO (0.808, p:0.15), FCO (r = 0.669, p<0.05) and negatively correlated with TA. The mean Abundance, Water temperature (WT), pH, dissolved oxygen (DO mg/L), free carbon dioxide (FCO2 mg/L) and Total alkalinity (TA mg/L) respectively 60.15%, 27.3°C, 6,7, 5.3 mg/L. 12.2 mg/L and 44.43 mg/L. Seasonal variation in the occurrence of these parasites are also effected by certain ecological conditions, particularly distribution of intermediate hosts and also the age of the host and the life cycle of the parasite species.